GeoGebra-Assisted discovery learning: an effective strategy to enhance elementary students' interest in learning plane area measurement - Basri, Hasan; García-García, Javier; Rodríguez-Nieto, Camilo Andrés; Rifanda, Akhmad Riski; Indahwati, Rohmah (Universitas Terbuka, 2025)
This study aimed to examine the difference in learning interest between students taught using the Discovery Learning model assisted by GeoGebra and those taught using conventional methods. The research employed an experimental method with a Posttest-Only Control Group Design, where the VA class acted as the experimental group and the VB class as the control group, each with 33 students. Data were collected using a learning interest questionnaire. The data was analyzed statistically by first carrying out normality and homogeneity tests on the data before carrying out the t-test. The results showed that the average learning interest score in the experimental group was in the very good category, while in the control group it was in the good category. The results of hypothesis testing with a significance level of 0.05 show that the Discovery Learning model assisted by GeoGebra has a significant effect on students' interest in learning, with this model generating higher interest compared to conventional learning methods.